Establishment of m7G-related gene pair signature to predict overall survival in colorectal cancer - Li, Kai; Wang, Weixing (Frontiers in Genetics, 2022)
Background: N7-methylguanosine (m7G) is an emerging research hotspot in the field of RNA methylation, and its role in tumor regulation is becoming increasingly recognized. However, its role in colorectal cancer (CRC) remains unclear. Hence, our study explored the role of m7G in CRC. Methods: The mRNA expression data and the corresponding clinical information of the patients with CRC were obtained from The Cancer Genome Atlas (TCGA). A m7G-related gene pair signature was established using the Cox and LASSO regression analyses. A series of in silico analyses based on the signature included analysis of prognosis, correlation analysis, immune-related analysis, and estimation of tumor mutational burden (TMB), microsatellite instability (MSI), and response to immunotherapy. A nomogram prediction model was then constructed. Results: In total, 2156 m7G-related gene pairs were screened based on 152 m7G-related genes. Then, a prognostic signature of seven gene pairs was constructed, and the patients were stratified into high- or low-risk groups. Better overall survival (OS), left-sided tumor, early stage, immune activity, and low proportion of MSI-low and MSI-high were all associated with a low risk score. High-risk patients had a higher TMB, and patients with a high TMB had a poor OS. Furthermore, the risk score was linked to immune checkpoint expression (including PD-L1), the tumor immune dysfunction and exclusion (TIDE) score, and chemotherapy sensitivity. We also created an accurate nomogram to increase the clinical applicability of the risk score. Conclusions: We identified an m7G pair-based prognostic signature associated with prognosis, immune landscape, immunotherapy, and chemotherapy in CRC. These findings could help us to better understand the role of m7G in CRC, as well as pave the path for novel methods to assess prognosis and design more effective individualized therapeutic strategies.